Intellectual Property Rights in Forestry and Agricultural Sectors in India - Mehta, Harsh; Ayoub Dar, M.; Rathore, A. C.; Chaturvedi, O. P. (Indian Forester, 2015)
Intellectual property rights play a vital role in research innovation and economy of the country. An attempt has been made to study the patenting scenario in India after the enforcement of product patent regims in 2005. The study is based on the data base of the Indian Patent Office, IPAIRS version 4.0 from 2005 to 2012. Maximum number of patents were obtained in the field of agricultural chemicals (A01N). The second most active area of research in agriculture was foodstuffs and non-alcoholic beverages, preparation or treatment, preservation of foods or foodstuffs (A23L) with 483 patents. Other prominent area, viz. (C09D) coating compositions, Dye, paints, polishes and natural resins, adhesive recorded as many as 294 and 190 (C09K) patents, respectively. New plants or processes for obtaining them and plant reproduction, followed by catching, trapping apparatus for destruction of noxious animals were other emerging areas in agriculture with 53, 51, 48, 47 and 16 patents indicating diversification in Indian agriculture/forestry sectors. Animal husbandry, silk rearing or breeding animals, new breeds (48), horticulture, cultivation of vegetables and forestry (47) (A01B). Soil working in agriculture or forestry, agricultural machines or implements registered 16 patents during the period. Assignee cross section of the granted patents revealed that maximum number of patents were obtained by the foreign companies and institution followed by Indian institutions and Indian companies. There was a sizeable share of individuals/foreign/Indian nationals holding patents in large areas of patenting in agriculture and forestry.